Agronomic characterization of citrandarin fruits and seeds - Schinor, Evandro Henrique; Arakaki, Marcelo; Cristofani-Yaly, Mariângela (Comunicata Scientiae, 2020)
In citrus cultivation, rootstocks are of fundamental importance and affect several characteristics of the variety used as canopy. Despite the great diversity within Citrus and related genera, the production of rootstocks in Brazil is restricted to a small number of varieties, making the citrus culture vulnerable to the appearance of phytosanitary problems. The aim of this study was to agronomically characterize fruits and seeds of seven citrandarins [Citrus sunki (Hayata) hort. ex Tanaka x Poncirus trifoliata cv. Rubidoux (L.) Raf.], obtained by controlled crossing. The orchard was installed in randomized blocks, with three replicates, in the municipality of Cordeirópolis, SP, where 20 fruits were collected in each replicate, obtained from free pollination of seven citrandarins, Swingle citrumelo and Rangpur lime. The following variables were evaluated: fruit mass, height, diameter, total number of seeds and percentage of viable seeds per fruit; number of embryos per seed, mass of one thousand seeds, number of seeds in 1.0 kg, final emergence rate, number of seedlings per seed, polyembryony rate, emergence speed index and seedling height at 60 days after sowing. For fruit size, the highest values were obtained for Swingle citrumelo. For number of embryos per seed, seedlings obtained through seed and polyembryony, citrandarin TSxPT 245 showed the highest values. Although citrandarin fruits had smaller size than fruits from commercial Rangpur lime and Swingle citrumelo rootstocks, characteristics related to seeds such as viability, polyembryony and emergence rate, were similar or superior, and can be considered potential new rootstocks for the production of citrus plants.